Role of inflammation and comorbidities in the association of heart failure with incident cancer in the HUNT3 cohort. (14th October 2021) - Bertero, E; Carmisciano, L; Jonasson, C; Maack, C; Ameri, P
Abstract: Background: Conflicting data exist regarding the risk of cancer in patients with heart failure (HF). It was first reported that incident cancer is more common among patients with than without HF, whereas more recent studies indicate that this association is primarily driven by comorbidities. HF, cancer, and comorbidities, such as chronic kidney disease (CKD) and chronic obstructive pulmonary disease (COPD), share numerous risk factors, including a state of chronic low-grade inflammation reflected by elevated circulating levels of pro-inflammatory cytokines. The objective of this analysis was to assess whether chronic low-grade inflammation, as measured by levels of high-sensitivity C-reactive protein (hsCRP), and comorbidities mediate the association of HF with incident cancer. Methods: We used data from the 3rd wave of the Nord-Trøndelag Health Study (HUNT3), a population-based study that enrolled 50, 803 individuals ≥18-year-old between October 2006 and June 2008 in the Nord-Trøndelag County (Norway), from the Cancer Registry of Norway and from the administrative health care records of the same region. Associations between baseline characteristics and the development of cancer were assessed using Cox proportional hazards regression models, using time from HUNT3 enrollment as the time scale. Analyses were performed using R statistical software, version 4.0.2. Results: In HUNT3, hsCRP was measured in 47, 571 individuals at the time of enrollment. Of these, we excluded 2, 308 patients because of missing information, leaving a cohort of 45, 263 subjects. Figure 1 shows the characteristics of the study population at baseline stratified by hsCRP tertiles. The prevalence of cardiovascular disease, comorbidities, and obesity was progressively higher with increasing concentrations of hsCRP. During a median follow-up of 12 years, there were 66/408 cases of incident cancer in patients with HF at baseline and 5, 024/47, 163 in subjects without HF, with a more than 2-fold (HR 2.30; 95% CI 1.80–2.93; p<0.001) increase in risk of developing cancer. After adjusting for age and sex, the excess risk decreased to 43% (HR 1.43; 95% CI 1.12–1.82). When including hsCRP in the model, the HF-related risk of cancer was 33% (HR 1.33; CI 1.04–1.70; p=0.022). Furthermore, when body mass index, CKD, COPD, and smoking and drinking habits were included in the model, the risk of cancer in HF patients compared to individuals without HF was no longer significant (HR 1.23; 95% CI 0.94–1.60; p=0.127). Age, male sex, hsCRP, COPD, obesity, and smoking habits were all associated with an increased risk of cancer (Figure 2). Conclusions: The increased risk of cancer in HF patients compared with the general population is at least in part explained by concomitant inflammation and comorbidities. Funding Acknowledgement: Type of funding sources: None.